(3edJbi GdCHMQ aj aQhY GdMfajIs - (3EHQGgje GdMdHj , HQgGf GdOjf EHQGgje Hf eMeO Hf EHQGgje GdMdHj,J (B956 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdeaJbQ Edi QMeI QHg GdZfi EHQGgje Hf eMeO Hf EHQGgje GdMdHi bO SCdfi HYV WGdHi GdESJaGOI Cf CLeY cJGHkG jTJed Ydi eSGFd GdbOhQi s
(3BNQgG (B:s
(3Ke Efi ROJ eSGFd cKjQI ef GdgOGjI hef eLeY GdHMQjf hGddg MSHi hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B80s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1814s
Keywords: (3Gdabg GdMfajs